2013
DOI: 10.1371/journal.pone.0079996
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Comparison Reveals Key Candidate Genes Responsible for the Unusual Reblooming Trait in Tree Peonies

Abstract: Tree peonies are important ornamental plants worldwide, but growing them can be frustrating due to their short and concentrated flowering period. Certain cultivars exhibit a reblooming trait that provides a valuable alternative for extending the flowering period. However, the genetic control of reblooming in tree peonies is not well understood. In this study, we compared the molecular properties and morphology of reblooming and non-reblooming tree peonies during the floral initiation and developmental processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Zhang et al (2013) identified 50,829 unigenes with an average length of 585 bp. Zhou et al (2013) generated 59,275 and 63,962 unigenes with mean sizes of 698 and 699 bp from 2 types of tree peonies, respectively. Compared with these 2 studies, we obtained a larger number of unigenes in the leaf transcriptome with longer or similar average lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2013) identified 50,829 unigenes with an average length of 585 bp. Zhou et al (2013) generated 59,275 and 63,962 unigenes with mean sizes of 698 and 699 bp from 2 types of tree peonies, respectively. Compared with these 2 studies, we obtained a larger number of unigenes in the leaf transcriptome with longer or similar average lengths.…”
Section: Discussionmentioning
confidence: 99%
“…However, the short reads generated by the Illumina platform can currently be assembled for a lower price, and a series of transcriptomes from non-model organisms have been successfully sequenced and assembled de novo (Li et al, 2012;Toledo-Silva et al, 2013). For tree peony, transcriptomes of petals and flower buds have been sequenced and millions of transcripts were obtained (Zhang et al, 2013;Zhou et al, 2013). Therefore, the Illumina platform is a preferable method for the transcriptome sequencing of peony leaves.…”
Section: Introductionmentioning
confidence: 99%
“…It also identified a large number of novel long non-coding RNAs and fusion transcripts [39]. At present, only NGS and SLAF-seq technologies have been applied frequently in tree peonies [40][41][42][43]. It is the first attempt to explore the carpel quantitative variation by SMLRS.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq has been successfully applied to many species, including Takifugu rubripes [21], Streptococcus mutans [22], Streptococcus mutans [23], Soybean [24] and tree peonies [25]. Here, we used RNA-Seq technology to characterize and identify the expression of a large number of genes, especially those expressed differentially during vernalization phase.…”
Section: Introductionmentioning
confidence: 99%